Mapping trends and hotspots of mitochondrial dysfunction in Alzheimer’s disease from 2013 to 2022: a bibliometric analysis of global research - Guo, Wang; Hassan, Liban Abdulle; Chu, Yu-hao; Yang, Xue-ping; Wang, Sheng-xue; Zhu, Han-xiao; Li, Yun (Frontiers in Neuroscience, 2023)
Objective Alzheimer’s disease (AD), a prevalent neurodegenerative affliction that predominantly affects the elderly population, imposes a substantial burden on not only patients but also their families and society at large. Mitochondrial dysfunction plays an important role in its pathogenesis. In this study, we conducted a bibliometric analysis of research on mitochondrial dysfunction and AD over the past 10 years, with the aim of summarizing current research hotspots and trends in this field. Methods On February 12, 2023, we searched for publications about mitochondrial dysfunction and AD in the Web of Science Core Collection database from 2013 to 2022. VOSview software, CiteSpace, SCImago, and RStudio were used to analyze and visualize countries, institutions, journals, keywords, and references. Results The number of publications on mitochondrial dysfunction and AD were on the rise until 2021 and decreased slightly in 2022. The United States ranks first in the number of publications, H-index, and intensity of international cooperation in this research. In terms of institutions, Texas Tech University in the United States has the most publications. The Journal of Alzheimer’s Disease has the most publications in this field of research, while Oxidative Medicine and Cellular Longevity have the highest number of citations. Mitochondrial dysfunction is still an important direction of current research. Autophagy, mitochondrial autophagy, and neuroinflammation are new hotspots. The article from Lin MT is the most cited by analyzing references. Conclusion Research on mitochondrial dysfunction in AD is gaining significant momentum as it provides a crucial research avenue for the treatment of this debilitating condition. This study sheds light on the present research trajectory concerning the molecular mechanisms underlying mitochondrial dysfunction in AD.